Parent Mental Health Problems and Motivation as Predictors of Their Engagement in Community-Based Child Mental Health Services - Haine-Schlagel, Rachel (Child Youth Serv Rev, 2019)
Parent or caregiver engagement in child mental health treatment is an important element of treatment effectiveness, particularly for children with disruptive behavior problems. Parent or caregiver characteristics, such as their mental health and/or motivation to participate in treatment, may impact engagement and subsequent treatment outcomes. However, a lack of empirical research exists examining these potential links, particularly in community-based treatment settings. The current pilot study: 1) examines whether parent mental health problems and/or early parent motivation to participate in treatment predict three indicators of parent engagement in child treatment, controlling for the other predictor; and 2) examines and compares the differential influence of parent mental health and parent motivation on each parent engagement indicator. Participants in this study include 19 dyads from 18 therapists who were recruited from community mental health clinics. Results indicated a significant association between parent mental health and session attendance, and a marginally significant association between parent mental health and therapist-rated parent engagement. Parent mental health predicted outcomes above and beyond parent motivation. These findings preliminarily suggest that parent mental health problems early in child mental health treatment may be important to consider as an impactful target to promote parent treatment engagement, in addition to focusing on parent motivation to participate in treatment.